Digitalisasi dan Pendampingan UMKM Binaan melalui Aplikasi Profil CMS Berbasis Website BUMDESMA Mentereng LKD - Dewanta, Favian; Rusdinar, Angga; Dwiputra Setiady, R. Rogers; Virgono, Agus; Isnawati, Anggun Fitrian; Kartika Delimayanti, Mera (Politeknik Negeri Jember, 2026)
The problem faced by the partner, the Mentereng LKD Village-Owned Enterprise (BUMDESMA) in Cikoneng District, was the limited ability to manage its fostered MSME data in a structured and digitalized manner. This made MSME-related information difficult to access and less than optimal in supporting business development. This community service program aimed to assist in the implementation of a website-based digital system to simplify the administration and management of MSME profile data. The methods used included business process mapping, needs assessment, CMS and Bootstrap-based application development, training for operators and fostered partners, and field trials. The results showed that this website-based MSME profile application was successfully implemented and well-received by BUMDESMA managers and fostered MSME partners. This application enables more organized data management, facilitates information access, and facilitates the management of fostered MSME data. Furthermore, the training activities increased the capacity of operators to manage the system independently. This program is expected to be the first step in supporting the digital transformation of MSME management at the village level.